Analisis strategi pengembangan industri sirup pokak di Probolinggo - Nita Kuswardhani; Nadia Putri Irkhana (AGROINTEK, 2025)
Indonesia is often known for its high local wisdom. One of these local wisdoms includes food potential. The potential of this food consists of a variety of foods as well as traditional drinks. Pokak Syrup is one of the traditional drinks made from a mixture of ginger, cloves, cinnamon, orange leaves, pandanus, sugar, lemongrass and other spices.  By processing from fresh ingredients into ready-to-consume products, Pokak Syrup is expected to increase the open up a better market and be competitive again in the midst of the current market. This study aims to develop a feasible business development strategy for further business development. This research uses IFAS and EFAS analysis techniques at the input stage, then mapped to the SWOT matrix and IE matrix at the matching stage, and finally QSPM analysis is carried out at the decision stage. The average VALUE of IFE was 2.78 and the average EFE was 3.00. The value indicates the position of quadrant II, which indicates that the strategy required for the company today is to “grow and build strategy”. Based on the results of the QSPM matrix, the highest attractiveness value is in Strategy 7 is to improve product quality and outlet facilities with a total amount of attractiveness (TAS) of 6,031. To improve product quality, you can choose the best quality raw materials and more hygienic processing so that the product is of high quality and the product has a longer shelf life. In the syrup industry, the main thing that needs to be considered is the arrangement of the room and the use of good room lighting, so that the product display becomes more attractive and consumers' interest in buying the product increases.